2004
DOI: 10.1111/j.0886-0440.2004.04009.x
|View full text |Cite
|
Sign up to set email alerts
|

Transbrachial Coil Occlusion of the Large Branch of an Internal Mammary Artery Coronary Graft

Abstract: Percutaneous transbrachial insertion of two complex coils into the intercostal branch of the left internal mammary artery resulted in the relief of severe angina in a 45-year-old man who had coronary artery bypass surgery 2 years before. The diagnosis of coronary artery steal was made clinically. This case illustrates the importance of recognizing coronary steal in patients who redevelop angina after coronary artery surgery with the use of an incompletely prepared left internal mammary artery as a conduit. Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This argument for a coronary steal phenomena as a cause of post‐CABG angina has been raised by many authors. Previous studies postulated that a coronary artery steal syndrome is more likely to occur if the side branch is larger than the distal LIMA graft, if there is a stenosis in the distal LIMA anastamosis, or if there is disease progression of the targeted native coronary artery [1–4]. Following open heart surgery, most surgeons ligate the proximal side branches of the LIMA [5], but a recent report in the surgical literature suggests that this might not be necessary [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This argument for a coronary steal phenomena as a cause of post‐CABG angina has been raised by many authors. Previous studies postulated that a coronary artery steal syndrome is more likely to occur if the side branch is larger than the distal LIMA graft, if there is a stenosis in the distal LIMA anastamosis, or if there is disease progression of the targeted native coronary artery [1–4]. Following open heart surgery, most surgeons ligate the proximal side branches of the LIMA [5], but a recent report in the surgical literature suggests that this might not be necessary [6].…”
Section: Discussionmentioning
confidence: 99%
“…A literature review from 1980 revealed 25 reports involving 43 patients who were identified as having a coronary artery steal syndrome due to a LIMA side branch. These patients underwent side‐branch occlusion through various interventions, primarily coil embolization and surgical ligation [1, 4]. The clinical outcomes in these reports have been favorable, with 31 of the 43 (72%) patients reported to have clinical improvement following the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review identified 43 patients with coronary steal syndrome due to a LIMA side branch. After side branch occlusion through coil embolization and surgical ligation, 3, 5 the clinical outcome was favorable in 31 patients. A stress test for ischemia using different modalities was performed in 15 patients before and after the procedure.…”
Section: Commentmentioning
confidence: 99%
“…The coronary steal syndrome is more likely to occur in the existence of (1) proximal unligated LIMA side branches if the side branch is larger than the distal LIMA graft, (2) stenosis in the distal LIMA anastomosis, and (3) disease progression of the targeted native coronary artery 2–5 . The hemodynamic significance and need for treatment of this phenomenon after LIMA bypass surgery remains controversial.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation